Efektivitas Edukasi Dini Menggunakan Leaflet Terhadap Peningkatan Pengetahuan Diabetes Melitus pada Siswa MTsS Nurhasanah Labuhan Ruku - Barus, Nency Utami Br; Mawandri, Dwi; Risma, Ade; Zahra, Fairuz; Susanti, Nofi; Indriani, Fatma (Yayasan Jompa Research and Development, 2025)
Diabetes Mellitus (DM) is a global and national health issue with a continuously rising prevalence. Data from the 2023 Indonesian Health Survey (SKI) indicates that the prevalence of DM in individuals aged ≥15 years has reached 11.7%. This increase highlights the crucial need for early education, especially among students. This study aims to evaluate the effectiveness of education using a leaflet medium in improving students' knowledge of DM. The research employed a quantitative method with a quasi-experimental approach and a one-group pretest-posttest design. The sample consisted of 31 seventh and eighth-grade students from MTsS Nurhasanah Labuhan Ruku, selected through total sampling. Knowledge was measured using a questionnaire administered both before (pretest) and after (posttest) the educational intervention with the leaflet. A bivariate data analysis using the Paired Samples Test revealed a significant increase in students' knowledge levels. Before the education, 71% of students had poor knowledge, which decreased to 16.1% after the intervention. Conversely, the percentage of students with good knowledge increased from 29% to 83.9%. The statistical test result showed a p-value of 0.0001, confirming a significant difference in student knowledge before and after the intervention. Therefore, this study concludes that education through a leaflet medium is effective in improving students' knowledge of diabetes mellitus.